Correlation of -Previous Advertisement Expenses- and -Total Sales-of Firms during the Big Recession - Tasar, Izzet; Demirel, Gokce; Kalayci, Irfan (Elsevier Science Bv, 2014)
We know that the global crises that is named Big Recession by IMF first resulted a sharp decrease in total demand. The sharp decrease in total demand is not anything different from the real equilibrium in the consumptions. It is obvious that the market conditions forces the individual consumption to an upper level by its instruments. The most important instrument is Advertisement. Paco Underhill; an environmental psychologist says: If we went into shops only when we needed to buy something, and if once in there we bought only what we needed, the economy would collapse, boom. We will use 20 companies as a sample for our research. We will try to show the correlation between the adv. Expenses and sales and try to find an answer if it is worse or better to make advertisement expenses in the previous period of such a recession. (C) 2014 The Authors. Published by Elsevier B.V.
International Conference on Emerging Markets Queries in Finance and Business -- OCT 24-27, 2013 -- Tirgu Mures, ROMANIA
Keywords: Big recession; advertisement expenses of firms; their total sales